A Remarkable cis‐ and trans‐Spanning Dibenzylidene Acetone Diphosphine Chelating Ligand (dbaphos). Issue 19 (11th March 2013) - Jarvis, Amanda G.; Sehnal, Petr E.; Bajwa, Somia E.; Whitwood, Adrian C.; Zhang, Xiangbiao; Cheung, Man Sing; Lin, Zhenyang; Fairlamb, Ian J. S.
Abstract A multidentate and flexible diolefin–diphosphine ligand, based on the dibenzylidene acetone core, namely dbaphos (1), is reported herein. The ligand adopts an array of different geometries at Pt, Pd and Rh. At PtII the dbaphos ligand forms cis‐ and trans‐diphosphine complexes and can be defined as a wide‐angle spanning ligand. 1H NMR spectroscopic analysis shows that the β‐hydrogen of one olefin moiety interacts with the PtII centre (an anagostic interaction), which is supported by DFT calculations. At Pd0 and RhI, the dbaphos ligand exhibits both olefin and phosphine interactions with the metal centres. The Pd0 complex of dbaphos is dinuclear, with bridging diphosphines. The complex exhibits the coordination of one olefin moiety, which is in dynamic exchange (intramolecular) with the other "free" olefin. The Pd0 complex of dbaphos reacts with iodobenzene to afford trans‐[PdII(dbaphos)I(Ph)]. In the case of RhI, dbaphos coordinates to form a structure in which the phosphine and olefin moieties occupy both axial and equatorial sites, which stands in contrast to a related bidentate olefin, phosphine ligand ("Lei" ligand), in which the olefins occupy the equatorial sites and phosphines the axial sites, exclusively.